Passive treatment of acid mine drainage using mixed substrates: batch experiments - Muhammad, Siti Nurjaliah; Mohd Kusin, Faradiella; Md Zahar, Mohd Syakirin; Halimoon, Normala; Mohamat Yusuf, Ferdaus (Elsevier, 2015)
Treatment of acid mine drainage (AMD) has been tested in batch experiments to evaluate the efficiency of both single and mixed substrates for mine-impacted waters. Synthetic mine water was used in all experiments. The single treatment was performed using limestone (LS), activated sludge (AS), and spent mushroom compost (SMC). In addition, different ratios of treatment media combined as mixed substrates were also tested for AMD in an anoxic condition. Physico-chemical parameters and heavy metals (Mn, Fe, Cu, Pb, Zn) were analyzed throughout 120 h. Hence, SMC showed great contribution in the process of AMD treatment in this study. The results showed that the mixed substrates were effective in removing heavy metals and sulfate i.e. uncrushed limestone mixed with AS, SMC and woodchips at 12 hours contact time with 88.15% of removal efficiency